REVENUE MANAGEMENT AND DISTRIBUTION OF ZAKAT, INFAQ, AND SADAQAH AT THE LAZISMU SERVICE OFFICE OF BMT ARTHA AMANAH SANDEN - Vikri Rizqa Putra; Rusdianto Rusdianto (SEAN Institute, 2023)
Zakat is a religious obligation that is included in the third pillar of Islam. In terms of implementation, zakat is a social obligation for the wealthy after their wealth has reached the minimum threshold (nishab) and after a year has passed (haul). Among the wisdom behind the legislation of zakat is to realize economic justice. This research aims to determine how the revenue management and allocation of ZIS funds are carried out at BMT Artha Amanah Sanden. This study used a qualitative method, with interviews conducted with several parties, including the daily supervisory board, the baitul maal manager, and the financial administrator at BMT Artha Amanah Sanden to achieve data validity through data triangulation. The results showed that BMT Artha Amanah uses fundraising and kencleng distribution methods for ZIS fund revenue, and its allocation focuses on empowering the community through the OHM DARMAN program as a platform to assist the community in the creative economy sector in the Bantul district area.